2018
DOI: 10.1007/s13280-017-1001-z
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture expansion in Brazilian freshwaters against the Aichi Biodiversity Targets

Abstract: The Convention on Biological Diversity proposed the Aichi Biodiversity Targets to improve conservation policies and to balance economic development, social welfare, and the maintenance of biodiversity/ecosystem services. Brazil is a signatory of the Aichi Biodiversity Targets and is the most diverse country in terms of freshwater fish, but its national policies have supported the development of unsustainable commercial and ornamental aquaculture, which has led to serious disturbances to inland ecosystems and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 72 publications
0
29
0
6
Order By: Relevance
“…This study showed that guppies are widespread in Brazil, mostly in the southeastern and northeastern regions. The use of this species for mosquito control and the relaxation of environmental laws has certainly contributed to its widespread introduction, even though the effectiveness of mosquito control is questionable (Azevedo‐Santos et al ., , ; El‐Sabaawi et al ., ), and Brazilian federal policies are contrary to international sustainable practices (Lima‐Junior et al ., ; Padial et al ., ; Pelicice et al ., ). In countries with megadiverse biotas, it is essential to take precautions to prevent new invasions and loss of native fish species.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that guppies are widespread in Brazil, mostly in the southeastern and northeastern regions. The use of this species for mosquito control and the relaxation of environmental laws has certainly contributed to its widespread introduction, even though the effectiveness of mosquito control is questionable (Azevedo‐Santos et al ., , ; El‐Sabaawi et al ., ), and Brazilian federal policies are contrary to international sustainable practices (Lima‐Junior et al ., ; Padial et al ., ; Pelicice et al ., ). In countries with megadiverse biotas, it is essential to take precautions to prevent new invasions and loss of native fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evaluations revealed that we should be concerned with the introduction of a “few widespread” species (Toussaint, Beauchard, et al., ), either unintentionally, because it culminates in biological invasions and biotic homogenization (Mazor et al., ; Pool & Olden, ; Toussaint, Charpin, et al., ). An outstanding example is the widespread occurrence of non‐native cichlid (Lima Junior et al., 2018) and cyprinid (Magalhães & Jacobi, ; Rodrigues‐Filho et al., ) fish in natural and artificial environments of South America and worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In fashioning romantic scenarios about South America (e.g., Valladão et al., ), Brazil points to the establishment of aquaculture as a central commodity (Lima Junior et al., ; Pelicice et al., ). The exploitation “below acceptable levels” defended by some authors (e.g., Saint‐Paul, ) generated a coordinated market that promoted the exponential multiplication of net cages in fresh waters, despite opposing scientific evidence, such as discussed by other authors (e.g., Alves, Vieira, Magalhães, & Brito, ; Lima Junior et al., ; Pelicice et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7. This is of concern since tilapiine cichlids, for example, members of the genera Coptodon, Oreochromis, and Tilapia, are the most widespread group of non-native fishes worldwide (Canonico et al 2005, Cassemiro et al 2018, presently cultured in most reservoirs of South America (Lima Junior et al 2018). Arrows and engines (in blue and black) indicate the intensity of processes and effects size.…”
Section: Discussionmentioning
confidence: 99%